Brand Management in the Business-to-Business (B2B) Context - Chen, Mobing (2012)
This research aims to explore how brand management influences business-to-business (B2B) companies in the form of new client acquisition. Keller’s customer-based brand equity model has been testified by Kuhn et al. to work in a single high-technology B2B industry. This research adapts the model to a different B2B market, a high-technology online service market. Specifically, the brand Testimonial Monkey and its clients are researched. The model is comprised of three steps, namely corporate brand equity, response and relationships and is validated in this industry. The practical implications for marketing practitioners and suggestions for further studies are discussed.